Tindak Tutur Direktif Humanis Langsung dalam Film “Anak Negeri Kisah Masa Kecil Ganjar Pranowo” - Nurlaili Irias Putri; Ida Zulaeha (Indonesian Language Education and Literature)
The purpose of this study was to analyze the form of direct speech acts and the function of explicit humanist directive speech acts. The data source in this research is the film “Anak Negeri Kisah Masa Kecil Ganjar Pranowo” by the director Mirwan Arfah. The data were collected using the observation method, basic tapping techniques, advanced technique of listening to the free to speak competently, and the advanced technique of note-taking. The validity of the data used triangulation: source, technique, and time. Data were analyzed using the practical matching method with the basic technique of sorting the determinants. Based on the mode, it includes: declarative, interrogative, and imperative. The function of direct humanist directive speech acts includes: asking, begging, inviting, asking, ordering, prohibiting, forgiving, and advising. Tujuan penelitian ini adalah menganalisis bentuk tindak tutur langsung dan fungsi tindak tutur direktif humanis langsung. Sumber data dalam penelitian ini adalah film “Anak Negeri Kisah Masa Kecil Ganjar Pranowo” Sutradara Mirwan Arfah. Data dikumpulkan dengan metode simak, teknik dasar sadap, teknik lanjutan simak bebas libat cakap (SBLC), dan teknik lanjutan catat.Keabsahan data menggunakan triangulasi: sumber, teknik, dan waktu. Data dianalisis menggunakan metode padan pragmatis dengan teknik dasar pilah unsur penentu (PUP). Berdasarkan modusnya, meliputi: deklaratif, interogatif, dan imperatif. Fungsi tindak tutur direktif humanis langsung, meliputi: meminta, memohon, mengajak, bertanya, memerintah, melarang, memaafkan, dan menasihati.